Irradiation alters extracellular vesicle microRNA load in the serum of patients with leukaemia - Hehlgans, Stephanie; Eckert, Denise; Martin, Daniel; Lumniczky, Katalin; Bug, Gesine; Rödel, Claus; Rödel, Franz (Strahlentherapie und Onkologie, 2024)
Purpose Recent data suggest an impact of extracellular vesicles (EVs) and their micro(mi)RNA cargo on cell-cell interactions to contribute to pathophysiology of leukaemia and radiation response. Here, we investigated differential miRNA cargo of EVs from serum derived from patients with leukaemia (n= 11) before and after total body irradiation with 2× 2Gy as compared to healthy donors (n= 6). Methods RNA was isolated from EVs and subjected to next generation sequencing of miRNAs. Analysis of sequencing data was performed with miRDeep29 software and differentially expressed miRNAs were filtered using R package edgeR10,11. Signaling pathways were identified using Kyoto Encyclopedia of Genes and Genomes database (KEGG) pathway analysis. Results Flow cytometric and Western blot analyses confirmed the presence of characteristic EV markers TSG-101, CD‑9 and CD-81. miRNA sequencing revealed a differential cargo in serum of patients with leukaemia in comparison to healthy donors with 23 significantly upregulated and 16 downregulated miRNAs affecting hedgehog, estrogen, glutathione metabolism and peroxisome proliferator-activated receptor (PPAR) signaling pathways amongst others. Whole body irradiation of patients with leukaemia significantly increased 11 miRNAs, involved in cell cycle regulation and platinum drug resistance, and decreased 15 miRNAs, contributing to apoptosis or cytokine-receptor interactions. Conclusion As compared to healthy controls and following irradiation, we have identified differentially regulated miRNAs in serum-derived EVs from patients with leukaemia that may serve as possible biomarkers of leukaemic disease and treatment and radiation exposure.
Gesehen am 21.01.2025